Teaching introductory physics - Arons, A. B. (Arnold B.) (New York : John Wiley and Sons, 1997)
This book is about: Guide to teaching for learning and understanding: Underpinnings; Rectilinear kinematics; Elementary dynamics; Motion in two dimensions; Momentum and energy; ...
Keywords: Physics; Physics -- Study and teaching